Genomic surveillance of genes encoding the SARS-CoV-2 spike protein to monitor for emerging variants on Jeju Island, Republic of Korea - Ha, Young-Ran; Kim, Hyun-Jeong; Park, Jae-Sung; Chung, Yoon-Seok (Frontiers in Microbiology, 2023)
The severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) pandemic has been fueled by new variants emerging from circulating strains. Here, we report results from a genomic surveillance study of SARS-CoV-2 on Jeju Island, Republic of Korea, from February 2021 to September 2022. A total of 3,585 SARS-CoV-2 positive samples were analyzed by Sanger sequencing of the gene encoding the spike protein before performing phylogenetic analyses. We found that the Alpha variant (B.1.1.7) was dominant in May 2021 before being replaced by the Delta variant (B.1.617.2) in July 2021, which was dominant until December 2021 before being replaced by the Omicron variant. Mutations in the spike protein, including N440K and G446S, have been proposed to contribute to immune evasion, accelerating the spread of Omicron variants. Our results from Juju Island, Republic of Korea, are consistent with and contribute to global surveillance efforts crucial for identifying new variants of concern of SARS-CoV-2 and for monitoring the transmission dynamics and characteristics of known strains.